Emissive polyelectrolytes as interlayer for color tuning and electron injection in solution-processed light-emitting devices - Tekoglu, Serpil; Petzoldt, Martin; Stolz, Sebastian; Bunz, Uwe H. F.; Lemmer, Uli; Hamburger, Manuel; Hernandez-Sosa, Gerardo (ACS applied materials & interfaces, 2016)
Herein we present a solution-processed hybrid device architecture combining organic light-emitting diodes (OLEDs) and light-emitting electrochemical cells (LECs) in a bilayer architecture. The LEC interlayer promotes the charge injection from an air-stable Ag cathode as well as permits the color tuning of the device emission. To this end, we used an alcohol-soluble anionic polyfluorene derivative, the properties of which were investigated by absorption and photoluminescence spectroscopy as well as by cyclic voltammetry. The bilayer device exhibited operating voltages ∼6 V and a color tuning of the emission spectrum dependent on the LEC interlayer thickness. The hybrid devices presented a color emission ranging from the yellow (x = 0.39, y = 0.47) toward the green region (x = 0.29, y = 0.4) of the Commission Internationale de I’Eclairage (CIE) 1931 chromaticity diagram.
Gesehen am 20.05.2020